Pengaruh Pembelajaran Learning-Cycle Terhadap Literasi Sains Siswa Kelas V Pada Materi Daur Air - Suryawanto, Arif Mishbah; Sujana, Atep; Sudin, Ali (Jurnal Pena Ilmiah, 2019)
The ability of science literacy is essential for every student to have, and is better applied since elementary school. Through learning using the Learning Cycle 7E model is a great way to improve science literacy skills, because in teacher learning activities facilitates students to find concepts independently. The purpose of this research is to identify differences in the influence of the model's Learning Cycle 7E and conventional to the ability of students ' science literacy in water-cycle materials. This research method is quasi experimental with the design of Nonequivalent control group design. The population of this research was all elementary school students in Arcamanik sub-district with research samples of SDN 141 Lokajaya V-B class as experimental class and V-A class as the control class. The instruments used in the research are science literacy skills tests, teacher performance observation sheets and student activities, polls, and interviews. As for the conclusion derived from this study, there is a significant difference in the skills of science literacy of students between learning using Learning Cycle 7E models and conventional learning.